Acculturation, urban identity, and psychological well‐being of rural–urban migrants in China. Issue 4 (12th December 2021) - Li, Yuxue; Chen, Juan; Xie, Shenghua; Huang, Xu
Abstract: Acculturation and identity are two significant determinants of the psychological well‐being of migrants, but how they interactively affect psychological well‐being is still underexplored. This study proposes an interactional perspective that links acculturation and urban identity to the psychological well‐being of rural–urban migrants in China. Using data from the 2014 National Migrant Population Dynamic Monitoring Survey, the results of multilevel modeling indicate that both acculturation and urban identity significantly affect the psychological well‐being of rural–urban migrants. Migrants who adopt the integration and assimilation strategy show better psychological well‐being than those who adopt the separation and marginalization strategy. Rural–urban migrants who have a stronger sense of urban identity show better psychological well‐being than those with a weaker sense of urban identity. Meanwhile, urban identity and acculturation also interactively affect the psychological well‐being of rural–urban migrants. In particular, urban identity alleviates the negative pressure generated in the process of acculturation for those who adopt the acculturation strategy of separation. In addition, the effect of acculturation and urban identity on the psychological well‐being of rural–urban migrants varies by migration distance. The research contributes to the literature by demonstrating that cultural identity and place identity interactively affect the psychological well‐being of internal migrants.